Environmental Social Work in Chile. Moving towards Green Social Work - Castañeda-Meneses, Patricia Lorena (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
Within the framework of the formation of the Green Social Work at international level, the article presents the results of a documentary research whose objective sought to characterize the situation of Chilean environmental Social Work, based on its historical background, their contributions in the hierarchies of environmental intervention and the main social problems derived from the environmental crisis that demand their specialized intervention. Qualitative documentary research was conducted organized by categories of analysis. The results indicate that Chilean environmental social work has incorporated environmental intervention strategies that seek to motivate the population to adopt behaviors that contribute to the preservation of natural resources, the protection of biodiversity and the application of environmental principles in their daily actions. It is concluded that the efforts of Chilean Social Work contribute to the international concept of Green Social Work and its declaration of caring for the planet as a professional duty.